2020
DOI: 10.3390/insects11090645
|View full text |Cite
|
Sign up to set email alerts
|

Diet Breadth Affects Bacterial Identity but Not Diversity in the Pollen Provisions of Closely Related Polylectic and Oligolectic Bees

Abstract: Mounting evidence suggests that microbes found in the pollen provisions of wild and solitary bees are important drivers of larval development. As these microbes are also known to be transmitted via the environment, most likely from flowers, the diet breadth of a bee may affect the diversity and identity of the microbes that occur in its pollen provisions. Here, we tested the hypothesis that, due to the importance of floral transmission of microbes, diet breadth affects pollen provision microbial community comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Our results suggest that the invasive wasp V. pensylvanica associates with a simple microbiome consisting largely of lactic acid bacteria and Zymobacter, along with significant associations of endosymbiotic bacteria. Notably, by comparing wasp colonies from two geographically-distinct locations, we also show that social wasp-associated microbial communities may contain environmentally-associated microbes similar to other Hymenoptera [17,18,29,50], and as…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results suggest that the invasive wasp V. pensylvanica associates with a simple microbiome consisting largely of lactic acid bacteria and Zymobacter, along with significant associations of endosymbiotic bacteria. Notably, by comparing wasp colonies from two geographically-distinct locations, we also show that social wasp-associated microbial communities may contain environmentally-associated microbes similar to other Hymenoptera [17,18,29,50], and as…”
Section: Discussionmentioning
confidence: 69%
“…We prepared paired-end 16S rRNA gene libraries for samples (N = 53) using a protocol based on Engel et al [48], Rothman et al 2018 [49] and 2020 [50], and McFrederick and Rehan 2016 [51]. Briefly, we generated libraries with a universal 16S primer sequence corresponding to the region 799-1115 (799F-mod3: CMGGATTAGATACCCKGG and 1115R: AGG GTTGCGCTCGTTG) chosen to avoid plant plastid contamination [52,53], a unique barcode sequence, and Illumina adapter sequence through two rounds of PCR.…”
Section: Dna Extractions and Library Preparationmentioning
confidence: 99%
“…Lactobacillus bxid5692 ASV 9) was detected at all locations in both bee species. Sampling location explained between 9-16% of variation in bacterial composition, more than previous studies examining geographic signatures in honey bees (Ge et al 2021) stingless bees (Liu et al 2021), and even some solitary Osmia (Rothman et al 2020). Although long-read sequences likely enable us to detect such patterns (Supplementary Table 1), distinctive Xylocopa sociality and patterns of microbial transmission may also contribute to geographic structuring.…”
Section: Discussionmentioning
confidence: 82%
“…While several studies have reported that the microbiome within the guts of adult social bees plays a significant role in maintaining bee fitness (Kwong et al, 2017 ; Kwong & Moran, 2016 ; Raymann & Moran, 2018 ), others suggest that the function of the gut microbiome alone is not sufficiently predictive of brood outcome (Gilliam et al, 1990 ; Martinson et al, 2012 ). In fact, mounting evidence across diverse bee species suggests that microbes occurring outside the bee gut, especially those within pollen/nectar provisions, harbor bacteria and fungi (Gilliam, 1997 ; McFrederick et al, 2013 ; Pimentel et al, 2005 ; Rosa et al, 2003 ; Yoder et al, 2017 ) that may be vital to larval nutrition (Steffan et al, 2019 ; Vannette et al, 2012 ), immune function (Kaltenpoth & Engl, 2014 ; McFrederick et al, 2014 ), and overall fitness (Cohen et al, 2020 ; Dharampal et al, 2019 ; Dharampal, Diaz‐Garcia, et al, 2020 ; Rothman et al, 2020 ; Steffan et al, 2017 ; Voulgari‐Kokota, McFrederick, et al, 2019 ; Voulgari‐Kokota et al, 2020 ). This phenomenon appears to be broadly applicable to global bee fauna, whether social (Anderson et al, 2014 ; Gilliam et al, 1989 ) or solitary (Gilliam et al, 1984 ; Graystock et al, 2017 ; McFrederick & Rehan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A vast body of literature has documented the presence of diverse exosymbiotic microbes associated with solitary bee species (Christensen et al, 2021 ; Dew et al, 2020 ; Gilliam, 1997 ; Graystock et al, 2017 ; Keller et al, 2013 ; McFrederick & Rehan, 2016 ; Rothman et al, 2020 ). It has been speculated that these exosymbionts likely perform vital nutritive and defensive functions that strongly influence bee health.…”
Section: Introductionmentioning
confidence: 99%